Pengaruh Sanitasi dan Konstruksi terhadap Kualitas Sumur Gali di Desa Sembubuk Kecamatan Jambi Luar Kota Kabupaten Muaro Jambi - Dirga Rangga Malindo; G M Saragih; Anggrika Riyanti (Jurnal Daur Lingkungan, 2020)
Efforts to monitor and supervise the quality of dug well water is an important part in meeting the need for clean water. This study is to determine the effect of sanitation and dug well construction on well water quality. Samples of well water quality were taken at wells with poor and poor sanitation and construction conditions based on SNI 03-2916-1992 concerning Dug Well Specifications. Water quality analysis was carried out in Jambi Province Regional Laboratory in accordance with Permenkes 32 of 2017 concerning About the environmental health quality standards and water health requirements for the needs of Sanitary Hygiene, Swimming Pool, Solus per Aqua, and Public Baths. Sanitation inspection to see the level of pollution risk refers to Permenkes Number 736 of 2010 concerning Management Procedures for Drinking Water Quality at dug well facilities. Laboratory test results show that wells with good sanitation and construction have good water quality compared to wells with poor sanitation and construction. However, both water quality samples still meet the Minister of Health Regulation 32 of 2017. Based on the results of sanitation inspection in the field as many as 63% of wells have a high level of pollution risk (High TRP), most of the dug wells have problems in their construction, to reduce the level of risk of dug well pollution needs improvement construction. In the planning and preparation of the Budget Plan for repairs to construction required a fee of Rp. 1,057,703,764, - these costs refer to Minister of Public Works Regulation No. 11 / PRT / M / 2013 Concerning guidelines for unit price analysis in the field of public works and repair of dug wells in accordance with SNI 03-2916-1992 Dug Well Specifications for Drinking Water Sources.